Anatomic and Thermometric Analysis of Cranial Nerve Palsy after Laser Amygdalohippocampotomy for Mesial Temporal Lobe Epilepsy. Issue 6 (25th September 2019) - Huang, Yuhao; Leung, Steven A; Parker, Jonathon J; Ho, Allen L; Wintermark, Max; Patel, Sohil H; Pauly, Kim Butts; Kakusa, Bina W; Beres, Shannon J; Henderson, Jaimie M; Grant, Gerald A; Halpern, Casey H
Abstract: BACKGROUND: Laser interstitial thermal therapy (LITT) is a minimally invasive therapy for treating medication-resistant mesial temporal lobe epilepsy. Cranial nerve (CN) palsy has been reported as a procedural complication, but the mechanism of this complication is not understood. OBJECTIVE: To identify the cause of postoperative CN palsy after LITT. METHODS: Four medial temporal lobe epilepsy patients with CN palsy after LITT were identified for comparison with 22 consecutive patients with no palsy. We evaluated individual variation in the distance between CN III and the uncus, and CN IV and the parahippocampal gyrus using preoperative T1- and T2-weighted magnetic resonance (MR) images. Intraoperative MR thermometry was used to estimate temperature changes. RESULTS: CN III (n = 2) and CN IV palsies (n = 2) were reported. On preoperative imaging, the majority of identified CN III (54%) and CN IV (43%) were located within 1 to 2 mm of the uncus and parahippocampal gyrus tissue border, respectively. Affected CN III and CN IV were more likely to be found < 1 mm of the tissue border ( PCNIII  = .03, PCNIV  < .01; chi-squared test). Retrospective assessment of thermal profile during ablation showed higher temperature rise along the mesial temporal lobe tissue border in affected CNs than unaffected CNs after controlling for distance (12.9°C vs 5.8°C; P  = .03; 2-sample t -test). CONCLUSION: CN palsy after LITT likely results from direct heating of the respective CN running at extreme proximity to the mesial temporal lobe. Low-temperature thresholds set at the border of the mesial temporal lobe in patients whose CNs are at close proximity may reduce this risk.